COVID-19 and Nursing Care of Ophthalmic Patients During Pandemic - Bhattarai, Shanjeev; Gautam Adhikari, Pragati (Journal of Nursing Education of Nepal, 2022)
Background: The corona virus, a novel, enveloped single stranded RNA virus (sarscOv-2) which has mainly affected respiratory system with life threatening results. The SARS-CoV-2 has been detected in several body fluids including tear and discharge of patients suffering from conjunctivitis. The aim of this paper is to explore the nursing care of person with ophthalmic problems.Methods: A literature review was conducted using data based of Google scholar, Google, Pubmed, Medline since 2015-2023.Results: An ophthalmic nurse can play a key role in teaching a patient and their attendants about general eye care and protection of vision during COVID-19 monitoring the patient’s condition, as well as ophthalmic instruments after it’s use have been are two main responsibilities of the nurse working in the ophthalmic units. Nurses also have responsibilities to maintain the safe and clean working environment of the unit, making the environment clean and safe.Conclusion: The environment of the eye ward must be clean, safe and free from organism. A nurse should warn the patients not to touch or rub the eyes and dressings or eye shields with unprotected hand during this COVID-19 pandemic.
Keywords: ACE 2; Conjunctivitis; Corona virus; COVID-19; Ocular manifestations; Ophthalmic nurses